Are objective measures of physical capability related to accelerated epigenetic age? Findings from a British birth cohort. Issue 10 (1st November 2017) - Simpkin, Andrew J; Cooper, Rachel; Howe, Laura D; Relton, Caroline L; Davey Smith, George; Teschendorff, Andrew; Widschwendter, Martin; Wong, Andrew; Kuh, Diana; Hardy, Rebecca
Abstract : Objectives: Our aim was to investigate the association of epigenetic age and physical capability in later life. Having a higher epigenetic than chronological age (known as age acceleration (AA)) has been found to be associated with an increased rate of mortality. Similarly, physical capability has been proposed as a marker of ageing due to its consistent associations with mortality. Setting: The MRC National Survey of Health and Development (NSHD) cohort study. Participants: We used data from 790 women from the NSHD who had DNA methylation data available. Design: Epigenetic age was calculated using buccal cell (n=790) and matched blood tissue (n=152) from 790 female NSHD participants. We investigated the association of AA at age 53 with changes in physical capability in women from ages 53 to 60–64. Regression models of change in each measure of physical capability on AA were conducted. Secondary analysis focused on the relationship between AA and smoking, alcohol, body mass index (BMI) and socioeconomic position. Outcome measures: Three objective measures of physical capability were used: grip strength, standing balance time and chair rise speed. Results: Epigenetic age was lower than chronological age (mean 53.4) for both blood (50.3) and buccal cells (42.8). AA from blood was associated with a greater decrease in grip strength from ages 53 to 60–64 (0.42 kg decrease per year of AA, 95% CI 0.03, 0.82 kg; p=0.03, n=152), but no associations were observed with standing balance time or chair rise speed. Current smoking and lower BMI were associated with lower epigenetic age from buccal cells. Conclusions: We found evidence that AA in blood is associated with a greater decrease in grip strength in British females aged between 53 and 60–64, but no association with standing balance time or chair rise speed was found.